Counterion influence on the N–I–N halogen bond1. Issue 7 (15th July 2015) - Bedin, Michele; Karim, Alavi; Reitti, Marcus; Carlsson, Anna-Carin C.; Topić, Filip; Cetina, Mario; Pan, Fangfang; Havel, Vaclav; Al-Ameri, Fatima; Sindelar, Vladimir; Rissanen, Kari; Gräfenstein, Jürgen; et al.
<x xml:space="preserve">Abstract</x> Counterions influence three-center halogen bonds differently than coordination bonds of transition metals.